The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1089/apc.2010.0173
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Use of HIV Pre-Exposure Prophylaxis Among Attendees of a Seattle Gay Pride Event and Sexually Transmitted Disease Clinic

Abstract: We surveyed a convenience sample of 215 HIV-negative men who have sex with men (MSM) recruited at a Gay Pride event and in an STD clinic about their willingness to use pre-exposure prophylaxis (PrEP). Overall, 44% reported that they would take PrEP every day if it helped prevent HIV. There was no association between sexual risk behavior and interest in taking PrEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 4 publications
4
66
2
Order By: Relevance
“…One possible reason is that they had stronger perceptions of risk behaviors because of their experience with STI. Our results were similar to those of a previous study in Seattle, 9 which showed that MSM recruited from STD clinics were more willing to use PrEP.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…One possible reason is that they had stronger perceptions of risk behaviors because of their experience with STI. Our results were similar to those of a previous study in Seattle, 9 which showed that MSM recruited from STD clinics were more willing to use PrEP.…”
supporting
confidence: 91%
“…The current survey shows that multiple sexual partners, unprotected anal sex, purchased or provided sexual services, and drug use were not associated with willingness to use PrEP, which is consistent with the two studies from Boston 7 and Seattle. 9 On the contrary, participants who did not or rarely found sexual partners on the Internet were more likely to be willing to use PrEP compared with higher risk participants, who often or sometimes found sexual partners on the Internet. These results indicate that high-risk behavior is not a predictor of the willingness to use PrEP.…”
mentioning
confidence: 98%
“…Although PrEP trials have shown efficacy for both MSM and heterosexual women and men, eight of the ten published surveys assessing awareness and attitudes toward the use of PrEP in U.S. populations were conducted exclusively with men who have sex with men (MSM) (Barash & Golden, 2010;Golub, Kowalczyk, Weinberger, & Parsons, 2010;Koblin et al, 2008;Liu et al, 2008;Mansergh et al, 2010;Mehta et al, 2011;Mimiaga, Case, Johnson, Safren, & Mayer, 2009;Voetsch, Heffelfinger, Begley, Jafa-Bhushan, & Sullivan, 2007); one with a primarily, but not exclusively, homosexual/bisexual male population (Kellerman et al, 2006), and only one with a largely heterosexual STD clinic population (Whiteside, Harris, Scanlon, Clarkson, & Duffus, 2011). These surveys elicited responses to discrete choice questions about anticipated use of PrEP and awareness of PrEP and were all conducted while trials were underway and efficacy results were not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have examined attitudes, awareness and willingness to use PrEP among MSM primarily in the U.S., [21][22][23][24][25][26][27][28][29][30][31] with more limited research in Australia, China, France, Thailand, UK, and Canada [32][33][34][35][36][37][38][39] through an individual lens, focusing on the individual characteristics of men that shape their desire and ability to use and adhere to PrEP. In general, this body of research has illustrated that MSM, and in particular high-risk MSM (those with multiple sex partners), have positive attitudes towards the adoption of PrEP as a HIV prevention strategy.…”
mentioning
confidence: 99%